Application of response surface method of optimization in flocculant assisted filtration of uranium bearing alkaline leach slurry of limestone origin. (5th June 2015) - Serajuddin, Md.; Sreenivas, T.
Abstract : Leach slurries of alkaline nature often show very low rate of filtration due to high pulp viscosity contributed by dissolved solutes in solution and very fine grained nature of the unleached solids. Maximisation of filtration performance generally needs exhaustive experimentation involving various parameters which influence the solid–liquid separation process. The study reported in this paper pertains to optimisation of parameters in vacuum filtration of uranium bearing alkaline leach slurry generated from a brecciated limestone ore using response surface methodology. The d 80 size of solids in the leach slurry is 60 μm and the pH of the pulp is 9·5–10. Initial screening of various commercial flocculants of anionic, cationic and non-ionic nature was carried out using the capillary suction time (CST) as basis. Minimum CST was achieved using a combination of anionic and non-ionic flocculant namely the Indfloc (IF) 477 and Guargum. The dosages of the flocculant combination and the slurry temperature were optimised to achieve maximum rate of filtration with optimal cake moisture under vacuum filtration conditions.